Cross-Regional Comparison of Trade Integration: The Case of Services - Shintaro Hamanaka (Asian Development Bank (ADB), 2013)
In this paper, we will examine the level of services trade integration in Asia in comparison with Europe and North America. The main empirical findings of this paper are that (i) the regional bias of services trade in Asia is as high or higher than in Europe and North America; (ii) in Asia, the regional bias of services trade is higher than that of goods trade, which is in sharp contrast to Europe and North America, where the regional bias of goods trade is higher than that of services trade; and (iii) while Asia's regional bias of goods trade shows a declining trend, that of services trade remains high, although in the future its decline is expected. Asia's relatively high-level of regional bias of services trade can be explained by the following factors: (i) a relatively high prevalence of a shared language (Chinese), which is essential to services trade, but not to goods trade; and (ii) the archipelagic nature of the region, which inhibits goods trade more than services trade. In contrast, for example, major European countries share land borders with their neighbors and they speak different languages. In order to deepen Asia's services trade integration, two policies are necessary. First, effective regional services agreements are critical to enhancing the level of integration. Second, policies to increase the trade of crisis-resilient services, such as professional services and insurance, as opposed to crisis-vulnerable services, such as transport and travel, are necessary.
hdl:11540/2326
Keywords: F15; 330; Services trade; regional integration; trade integration; determinants of trade; regional bias; regional trade agreement (RTA); Dienstleistungshandel; Regionale Wirtschaftsintegration; Handelsabkommen; Asien; Vergleich; Europa; Nordamerika